The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.cub.2012.08.048
|View full text |Cite
|
Sign up to set email alerts
|

A Permissive Role of Mushroom Body α/β Core Neurons in Long-Term Memory Consolidation in Drosophila

Abstract: We propose that these α/β core neurons serve as a "gate" to keep LTM from being formed, whereas any experience capable of "opening" the gate is given permit to be consolidated into LTM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 51 publications
(78 reference statements)
4
78
2
Order By: Relevance
“…S4F). Also, neurotransmission outputs from core α/β neurons (20) and MB-V3 neurons are both necessary during a delayed time period after spaced training for LTM formation. Altogether, these data show direct structural connectivity and are suggestive of potential functional connectivity between α/β MB neurons and MB-V3 neurons.…”
Section: Resultsmentioning
confidence: 99%
“…S4F). Also, neurotransmission outputs from core α/β neurons (20) and MB-V3 neurons are both necessary during a delayed time period after spaced training for LTM formation. Altogether, these data show direct structural connectivity and are suggestive of potential functional connectivity between α/β MB neurons and MB-V3 neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The procedures were described previously (71). For RU486 feeding (RU + ), flies were fed with 500 μM RU486 (mifepristone; J&K Chemicals) dissolved in control solution.…”
Section: Methodsmentioning
confidence: 99%
“…A current working model suggests that concomitant reward signals from sugar ingestion cause associative plasticity in Kenyon cells that might underlie memory formation (14-20). A single activation session of a specific cluster of dopamine neurons (PAM neurons) by sugar ingestion can induce appetitive memory that is stable over 24 h (19), underscoring the importance of sugar reward to the fly.The mushroom body (MB) is composed of the three different cell types, α/β, α′/β′, and γ, which have distinct roles in different phases of appetitive memories (11,(21)(22)(23)(24)(25). Similar to midbrain dopamine neurons in mammals (26,27), the structure and function of PAM cluster neurons are heterogeneous, and distinct dopamine neurons intersect unique segments of the MB lobes (19,(28)(29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…Recent studies have revealed aspects of the molecular and cellular mechanisms of LTM formation induced by repetitive training (8)(9)(10)(11), but how a single training induces a stable LTM is poorly understood (12).…”
mentioning
confidence: 99%